(untitled) (Research, Society and Development, 2025)
Introduction: Alzheimer’s disease (AD) represents a growing challenge in Brazil, characterized by cognitive deficits such as recent memory loss, disorientation, aphasia, and agnosia, and behavioral symptoms such as apathy and anxiety, aggravated by the chronic use of psychotropic drugs such as Zolpidem in the elderly. Objective: To analyze the prevalence of hospitalizations and deaths due to AD and estimate the chronic use of Zolpidem in the elderly (≥ 60 years) between 2020 and 2024. Methodology: Descriptive study with data from the SUS Hospital Information System, using statistical tests to assess the prevalence of hospitalizations and deaths due to AD, associated costs, and estimate the chronic use of Zolpidem. Results: Thousands of hospitalizations for AD were recorded, with a high mortality rate and female predominance, generating significant costs for the SUS. Chronic use of Zolpidem, common in the elderly, was associated with cognitive risks. Conclusion: AD imposes a significant burden on the Brazilian Unified Health System (SUS), intensified by the use of Zolpidem, requiring cautious management. Future studies should explore regional factors and non-pharmacological alternatives for insomnia, promoting safer care.